Dimethylarginine dimethylaminohydrolase 1 is involved in spinal nociceptive plasticity. Issue 10 (October 2015) - D'Mello, Richard; Sand, Claire A.; Pezet, Sophie; Leiper, James M.; Gaurilcikaite, Egle; McMahon, Stephen B.; Dickenson, Anthony H.; Nandi, Manasi
Abstract : Abstract: Activation of neuronal nitric oxide synthase, and consequent production of nitric oxide (NO), contributes to spinal hyperexcitability and enhanced pain sensation. All NOS isoforms are inhibited endogenously by asymmetric dimethylarginine, which itself is metabolised by dimethylarginine dimethylaminohydrolase (DDAH). Inhibition of DDAH can indirectly attenuate NO production by elevating asymmetric dimethylarginine concentrations. Here, we show that the DDAH-1 isoform is constitutively active in the nervous system, specifically in the spinal dorsal horn. DDAH-1 was found to be expressed in sensory neurons within both the dorsal root ganglia and spinal dorsal horn; L-291 ( N G –[2-Methoxyethyl]-L-arginine methyl ester), a DDAH-1 inhibitor, reduced NO synthesis in cultured dorsal root ganglia neurons. Spinal application of L-291 decreased N -methyl-D-aspartate–dependent postdischarge and windup of dorsal horn sensory neurons—2 measures of spinal hyperexcitability. Finally, spinal application of L-291 reduced both neuronal and behavioral measures of formalin-induced central sensitization. Thus, DDAH-1 may be a potential therapeutic target in neuronal disorders, such as chronic pain, where elevated NO is a contributing factor. Abstract : Supplemental Digital Content is Available in the Text.Inhibition of dimethylarginine dimethylaminohydrolase 1 attenuates pain-related behavior and hyperexcitability in pain conditions associated with excessive nitric oxide production, representing a novel therapeutic target.